Pengaruh Pelatihan, Budaya Organisasi, Kecerdasan Buatan Terhadap Manajemen Talenta (Studi Kasus di ORMAWA FEB UNISMA) - Taufiqurrahman, Mohammad; Khalikussabir, Khalikussabir; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to explore and evaluate the influence of training, organizational culture, and artificial intelligence on talent management (case study at ORMAWA FEB UNISMA). This research uses a quantitative approach using a Likert scale as a measuring tool. The sample was selected using purposive sampling, consisting of 74 Gen Z respondents. Primary data was collected through a questionnaire distributed via Google Forms. Data analysis includes validity and reliability tests, classical assumption tests, multiple linear regression, hypothesis tests, and determination tests carried out using SPSS 25 software. The research results reveal that training, organizational culture, and artificial intelligence each have a partial influence on talent management.Keywords: Training, Organizational culture, artificial intelligence, and Talent Management